Pinecone 1962 - Valdosta State College (Valdosta State College, 1962)
...for it is the most important time of your life. It is a day of search and discovery. The past was of great significance, and you must live up to what has been left, but you are the future. What you do with your college life will live on. Your potential is unlimited. '"Look well therefore to this day." The staff of the 1962 Pine Cone presents a record of this day.
A year book was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; Americana; University History